Impact of COVID-19 pandemic on international higher education and student mobility: Student perspectives from mainland China and Hong Kong. (2021) - Mok, Ka Ho; Xiong, Weiyan; Ke, Guoguo; Cheung, Joyce Oi Wun
Highlights: COVID-19 pandemic significantly decreased international student mobility. Mainland China and Hong Kong university students lack interests in overseas study. East Asia countries and regions become popular studying abroad destinations. Health and safety become students' primary concerns for studying abroad. Post-pandemic management becomes a key factor in attracting international students. Abstract: The study critically examines how students in Mainland China and Hong Kong conceive overseas studies plans against the COVID-19 crisis. Amongst the 2739 respondents, 84 % showed no interest to study abroad after the pandemic. For those respondents who will continue to pursue further degrees abroad, Asian regions and countries, specifically Hong Kong, Japan and Taiwan, are listed in the top five, apart from the US and the UK. The pandemic has not only significantly decreased international student mobility but is also shifting the mobility flow of international students. This article also discusses the policy implications, particularly reflecting on how the current global health crisis would intensify social and economic inequalities across different higher education systems.